2022
DOI: 10.2478/adms-2022-0021
|View full text |Cite
|
Sign up to set email alerts
|

Density and Water Absorption Coefficient of Sandcrete Blocks Produced with Waste Paper ash as Partial Replacement of Cement

Abstract: The literature is flooded with scientific information on most durability properties except water absorption coefficient of masonry units like sandcrete blocks. Also, while waste papers disposal is a systemic problem due to ineffectiveness of waste management system in developing countries, the price of cement is on the increase. This situation, ultimately, causes a bane in achievement of low-cost housing development considering the fact that sandcrete blocks are predominantly used as walling elements for such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Recently, it has been reported that waste paper ash (WPA) can be used to modify the plaster of Paris (POP) ceiling for improved performance [14]. Also, the utilization of WPA as a partial cement replacement material can improve the compressive strength of masonry materials such as concretes [15][16][17][18] and concrete blocks [19]. WPA is an effective stabilizer of clay soil for either road construction [20] or building design [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that waste paper ash (WPA) can be used to modify the plaster of Paris (POP) ceiling for improved performance [14]. Also, the utilization of WPA as a partial cement replacement material can improve the compressive strength of masonry materials such as concretes [15][16][17][18] and concrete blocks [19]. WPA is an effective stabilizer of clay soil for either road construction [20] or building design [3].…”
Section: Introductionmentioning
confidence: 99%
“…Even with that, the fiber is under-utilized. Since ineffective solid waste management systems persist in developing countries [25,26], the fiber is prevalently disposed of by open burning or indiscriminate dumping which eventually causes significant environmental problems. For the fact that the fiber generation will continue to rise from 21,560,251 tons in 2020 to about 30,732,801 tons in 2030 due to increasing demand of crude palm oil [27], the present situation is of great concern.…”
Section: Introductionmentioning
confidence: 99%